A corrigendum to “Hereditary properties between a ring and its maximal subrings” - Gaur, A.; Kumar, R. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
Let R be a commutative ring with identity. In [2] (Proposition 3.1), Azarang proved that if R is an integral domain and S is a maximal subring of R, and is integrally closed in R, then dim(S) = 1 implies that dim(R) = 1 if and only if (S : R) = 0. An example is given which shows the above mentioned proposition is not correct.